1999
DOI: 10.1523/jneurosci.19-19-08560.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Illusory and Real Contours in Human Cortical Visual Areas Revealed by Functional Magnetic Resonance Imaging

Abstract: Illusory contours (perceived edges that exist in the absence of local stimulus borders) demonstrate that perception is an active process, creating features not present in the light patterns striking the retina. Illusory contours are thought to be processed using mechanisms that partially overlap with those of "real" contours, but questions about the neural substrate of these percepts remain. Here, we employed functional magnetic resonance imaging to obtain physiological signals from human visual cortex while s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
244
6
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(300 citation statements)
references
References 54 publications
47
244
6
3
Order By: Relevance
“…In the present experiment and in our previous study (Martinez et al, 2006), source analyses of the N1 associated with object-selective attention also indicated a principal neural generator in lateral occipital cortex (area LOC). Activation in this same LOC region has been observed in numerous object recognition studies using a variety of task stimuli, including objects defined by illusory contours (Mendola et al 1999;Murray et al 2004), partially occluded objects (Lerner et al 2001) and scrambled objects (Malach et al 1995). On the basis of these studies and others it has been suggested that the LOC region plays an important role in the encoding and recognition of objects.…”
Section: Discussionmentioning
confidence: 58%
“…In the present experiment and in our previous study (Martinez et al, 2006), source analyses of the N1 associated with object-selective attention also indicated a principal neural generator in lateral occipital cortex (area LOC). Activation in this same LOC region has been observed in numerous object recognition studies using a variety of task stimuli, including objects defined by illusory contours (Mendola et al 1999;Murray et al 2004), partially occluded objects (Lerner et al 2001) and scrambled objects (Malach et al 1995). On the basis of these studies and others it has been suggested that the LOC region plays an important role in the encoding and recognition of objects.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, the IC effect is insensitive to variations in the contrast polarity (i.e. whether inducers are black on a gray background or vice versa) [8] (see also [39]), ruling out an explanation in terms of perceived brightness enhancement (see also [40]). The IC effect is mediated by the presence of the illusory figure but not collinear lines [41].…”
Section: Electroencephalography and Magnetoencephalographymentioning
confidence: 99%
“…In agreement are data concerning the relative insensitivity of IC processes to the spatial frequency of the misaligned gratings used as inducers (cf. Figure 6 in [40] as well as [55] for corresponding single-unit data).…”
Section: The Salient Region Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…These results were replicated by DeYoe et al (1996) and Engel et al (1997), also utilizing a cortical surface-based analysis but manually distinguishing the borders based on polar-angle information. Further phase-encoded mapping studies with modifications of the stimulus revealed visual areas V3A (DeYoe et al, 1996;Tootell et al, 1997Tootell et al, , 1998c, V3B (Press et al, 2001;Smith et al, 1998), V7 (Mendola et al, 1999;Press et al, 2001;Tootell et al, 1998a,c;Tootell and Hadjikhani, 2001), V8 , a putative homologue of the lateral intraparietal area (LIP) (Sereno et al, 2001), and retinotopic organization in human MT/V5 (Huk et al, 2002).…”
Section: Introductionmentioning
confidence: 99%